Optimal placement and sizing of multiple FACTS devices installation - Jumaat, S.A.; Musirin, I.; Othman, M.M.; Mokhlis, Hazlie (2012)
This paper presents optimal placement and sizing of multiple FACTS devices based on computational intelligence techniques. In this study, particle swarm optimization (PSO) and Evolutionary Programming (EP) approach is proposed to minimize the transmission loss in the power system with flexible AC transmission systems (FACTS) devices. Two types of FACTS are used: static var compensator (SVC) and thyristors controlled series compensator (TCSC) are two FACTS devices chosen for the optimal installation for compensation purposes due to reported promising performances of the devices. Experiment results on the IEEE 30 bus system with FACTS devices show that the proposed PSO approach can obtain better solutions than EP technique.